2020
DOI: 10.1086/710079
|View full text |Cite
|
Sign up to set email alerts
|

“Why Did They Die?”

Abstract: In the second half of the twentieth century, Indigenous populations from different parts of the world were identified as key subjects in a wide range of investigations into patterns of human biological variation. Focusing on Amazonia, a prominent region for such research, this paper explores some of the complex relationships between biomedicine, anthropological knowledge, political regimes, and Indigenous rights. We focus on the roles of Francis L. Black (Yale University) and James V. Neel (University of Michi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Authors also reported that mortality associated with disease outbreaks originating in urban areas take longer to reach indigenous communities ( 5 ). Furthermore, the “Virgin-soil” hypothesis, which proposes that indigenous populations that had no previous contact with certain pathogens, upon first exposure would be highly susceptible to disease due to lack of preestablished immunity, is unsubstantiated by scientific evidence ( 21 , 22 ). Beyond genetics, other factors exert a significant effect over the health of indigenous population in Brazil, such as economy, geographical location, contact with non-indigenous people, sanitation and access to basic health assistance ( 4 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Authors also reported that mortality associated with disease outbreaks originating in urban areas take longer to reach indigenous communities ( 5 ). Furthermore, the “Virgin-soil” hypothesis, which proposes that indigenous populations that had no previous contact with certain pathogens, upon first exposure would be highly susceptible to disease due to lack of preestablished immunity, is unsubstantiated by scientific evidence ( 21 , 22 ). Beyond genetics, other factors exert a significant effect over the health of indigenous population in Brazil, such as economy, geographical location, contact with non-indigenous people, sanitation and access to basic health assistance ( 4 , 23 ).…”
Section: Discussionmentioning
confidence: 99%